Soil Chitinolytic Bacteria from Jambi Province to Produce Antifungal of Plant Pathogens - Risky Hadi Wibowo; Sipriyadi Sipriyadi; Nisa Rachmania Mubarik; Iman Rusmana (Universitas Wiralodra, 2020)
Chitinolytic bacteria are bacteria that have chitinolytic activity, which is able to hydrolysis the composition of chitin which composes many fungal cell walls. Chitinolytic bacteria are currently more widely used because of their ability as a biological control agent to the pathogenic fungi especially in horticultural and plantation crops. This research was conducted with the aim of obtaining isolates of chitinolytic bacteria that were able to inhibit the growth of plant pathogenic fungi in Vitro on chitin agar media. Fusarium oxysporum, Sclerotium rolfsii, and Rhizoctonia solanii are used in the inhibition test of chitinolytic bacteria. Bacteria were isolated and screened from the soil of Bukit Dua Belas National Park and Oil Palm Plantations in Jambi using 0.3% chitin agar media. The results showed that two of 10 bacterial isolates were able to produce inhibition zones to the growth of hyphae of pathogenic fungi on potato dextrose agar (PDA) media. TB04-13 isolate was able to produce the largest inhibition in F. oxysporum and R. solanii about 42% and 42.05% respectively, while TB04-15 isolate produced the biggest inhibition in S. Rolfsii ranged to 25.50%. Based on the chitinolytic index (CI) values, isolates TB04-13 and TB04-15 produced CI values ​​of 1.60 and 0.63, respectively. The morphological characteristics and Gram staining of both TB04-13 and TB04-15 chitinolytic isolates are included in rod-shaped and Gram-positive bacteria. Both of these isolates can be used as antifungal-producing candidates for plant pathogenic fungi in Indonesia.